Contribution of Sex Differences to HIV Immunology, Pathogenesis, and Cure Approaches - Moran, Jose A.; Turner, Shireen R.; Marsden, Matthew D. (Frontiers in Immunology, 2022)
Approximately 38 million people were living with human immunodeficiency virus (HIV) in 2020 and 53% of those infected were female. A variety of virological and immunological sex-associated differences (sexual dimorphism) in HIV infection have been recognized in males versus females. Social, behavioral, and societal influences play an important role in how the HIV pandemic has affected men and women differently. However, biological factors including anatomical, physiologic, hormonal, and genetic differences in sex chromosomes can each contribute to the distinct characteristics of HIV infection observed in males versus females. One striking example of this is the tendency for women to have lower HIV plasma viral loads than their male counterparts early in infection, though both progress to AIDS at similar rates. Sex differences in acquisition of HIV, innate and adaptive anti-HIV immune responses, efficacy/suitability of specific antiretroviral drugs, and viral pathogenesis have all been identified. Sex differences also have the potential to affect viral persistence, latency, and cure approaches. In this brief review, we summarize the major biological male/female sex differences in HIV infection and their importance to viral acquisition, pathogenesis, treatment, and cure efforts.